Reduction of vibrations in electromechanical drive systems with vector control - Bachorz, Paweł; Switoński, Eugeniusz; Meżyk, Arkadiusz (Transport, 2004)
This paper presents the issues of modelling electromechanical drive systems in a mechatronic approach. The effect of a vector control system on the dynamics of the system is shown. The optimisation of the system in order to minimise vibration amplitudes and amplitudes of forces in selected kinematic pairs of a high power drive system was performed with the use of genetic algorithms. Design variables of the optimisation process comprised the structural parameters of the mechanical part as well as the settings of PI controllers of the vector control system. The selected results of numerical computations are presented. First Published Online: 27 Oct 2010